KONSTRUKSI KEBEBASAN MEDIA MASSA BARAT SEBAGAI BUDAYA POPULER: ANALISA TERHADAP BERITA DAN KARIKATUR NABI SAW DI MAJALAH CHARLIE HEBDO - Kun Wazis (Al'Adalah, 2015)
The mass media have effective force to influence of thought and behavior of communicant. With energy primarily of news, opinion, and advertising driven, the mass media capable of engendering portrait of independent. By it’s freedom perspective whatever constructed by mass media. Freedom of the West media addressed to Islam. One of them, repeatedly western media expose news and opinion that cornered islam and muslims. Chalie hebdo is a prime example of the vicious way communications products west mass show the images or prophet caricature as figures negative media. Although often get protest from muslims worldwide, magazine satire french origin deliberately repeating the publication vile against prophet. This paper to provide descriptive review of reality freedom western media has become popular culture by taking cases preaching and a caricature of the Prophet Muhammad on the magazine charlie hebdo. Thus, it can be seen clearly, po-sition and attitude muslims would be seeing reality news and opinion in the West newspapers.